The mitral bioprothesis implantation in patient with critical stenosis, a significant case history and coagulological complications - Ostrowski, Stanisław; Marcinkiewicz, Anna; Kośmider, Anna; Zwoliński, Radosław; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Mitral stenosis is a rare cause of a bioprothesis implantation. Rheumatic disease maintains the most common cause of it. Degenerative disease of the mitral valve develops with age. Clinical presentation often includes tricuspidal insufficiency and atrial fibrillation. In 2009 a 70-year-old woman with a diagnosed critical mitral stenosis, blindness in both eyes and hypertension was admitted to the Cardiac Surgery Clinic of the Medical University in Lodz. In the case history she had also gastrectomia, peritonitis with temporal sigmoideostomia and pulmonary edema. The patient underwent biological valve implantation in the extracorporeal circulation. After the operation massive drainage continued and coagulological disorders appeared, what was the cause of rethoracotomy and demanded intensive treatment with blood products and coagulation factors. Patient stabile condition was achieved. Early postoperative period was complicated by atrial fibrillation, acute renal failure and respiratory failure. Antyarythmic treatment, fluid management and mechanical assisted respiration allowed to normalize patient condition. In one and the half year observation the patient is in good clinical condition.